Empowering Students’ Autonomous Learning through Self-regulation, Metacognitive Strategies, and Collaborative Learning Environments - Paethrangsi, Nisara; Teekasap, Sombat; Khiewpan, Rachapong; jandaboue , Wanlapa (Journal of Liberal Arts RMUTT, 2024)
This article presents the enhancement of autonomous learning among learners using self-regulation strategies, metacognition, and a cooperative learning environment. These elements contribute to higher academic achievement. Promoting learners to enhance their knowledge of self-regulation and developing metacognitive skills in a cooperative learning environment is important for student learning in the 21st century. It helps learners spend time outside of universities to develop their knowledge and understanding. These skills are necessary for lifelong learning. This study shows that to promote students’ autonomy, teachers need to develop new teaching strategies and encourage students to have skills in planning, teamwork, self-reflection, and self-assessment, as well as time management with technology and effective communication. Recognizing the value of self- autonomous learning is essential for students. To transition from being passive recipients of information from lecturers to actively seeking knowledge and continuously learning independently, learners must embrace new learning strategies.